ANALYSIS ON CLASSIFICATION OF FOOTBALL TECHNIQUE - Slaidiņš, Kristaps; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Football is a situation sport where football players are characterized by a great variety and complexity of activities during the game, both in contact with the opponent and in the immediate vicinity of the opponent, while cooperating with other teammates. Sports scientists and coaches need to find out more about the set of techniques, its diversity and the amount of technique in top level football games in order to guide the optimal planning and implementation of the training process in the technical training of football players. Due to the diversity of techniques used by football players, there are different approaches to the classification of these techniques. However, it is very important to group all techniques according to their common features in order to adequately assess the structure of a football game, its development tendencies and issues. Research aim: to compare and analyse the essence of the classification of football technique and its development tendencies. Research methods: analysis of scientific articles (electronic scientific databases ScienceDirect, Google Scholar), search keywords – football, football technique, classification of football technique. Main results of the research:  two main approaches dominate in the classification of football technique: the technique approach and the game approach. Initially, football technique was mainly grouped by taking into account the player’s actions with or without the ball, the level of difficulty of the technique element, the role of the players and the player’s actions on the spot or in motion. As football develops, football technique is classified by taking into account the effectiveness of its application in specific tactical situations.